Incorporating Cognitive Behavioural Therapy into a Public Health Care System: Canada and England Compared - Noushon Farmanara; Gregory P. Marchildon; Amélie Quesnel-Vallée (McMaster University Library Press, 2016)
Since the second half of the 2000s, Canada and England have instituted differing reforms to address the inadequate provision and quality of mental health services in both nations. With growing evidence demonstrating the success and cost-effectiveness of psychotherapy, the English reform sought to expand the delivery of psychological services through the Improving Access to Psychological Therapies program (IAPT) focusing on cognitive behavioural therapy (CBT). In contrast, Canadian interventions at the federal level were centred on knowledge exchange and advocacy, primarily through the Mental Health Commission of Canada. While significant improvements were made during this period to increase CBT access in England, there continues to be an insufficient availability of psychological services to meet the growing need in Canada. While a national roll-out akin to the IAPT program in England is unlikely in Canada, similar reforms could be initiated at the provincial level of government. Indeed, several provincial governments have acknowledged the need for an expansion of CBT services and, over the last decade, some have tried to make CBT techniques more widely accessible. We review the case of the Bounce Back program developed in British Columbia (BC) to illustrate this potential in the Canadian context. Best practices indicate that care is needed beyond the provision of psychiatric services and pharmacotherapy alone, and the initial results of both the IAPT program and BC's Bounce Back program strongly suggest that it is possible to provide these cost-effective services in a public system.